STUDI REPRODUSIBILITAS POLA PUNCAK KROMATOGRAM AKIBAT PENGARUH VARIASI PH DAN LAMA WAKTU EKSTRAKSI DENGAN MENGGUNAKAN CAPSUL D SEBAGAI MODEL - Budiputra, Dewa Ken; Suirta, I Wayan; Sumarjaya, I Wayan (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2014)
The TLC chromatogram peak pattern reproducibility of the contained D capsule was carried out. The pH and time extraction was varied. The extracted substances were spotted on the Al TLC SiGF254 plate, than it was eluted with TB mobile phase (cyclohexane: toluene: diethylamine 75:15:10 v/v). The extraction methods were liquid-liquid extraction with extraction time variation (15 minute, 30 minute, 45 minute and 60 minute) and solid phase extraction with pH variation (pH 10, pH 11 and pH 12). The extraction time influenced the TLC peak pattern. The substances were optimal extracted after 30 minutes extraction. There was no variation in the peak pattern after 30 minutes extraction. The pH value variation did not affected the peak pattern reproducibility.
Keywords: Peak pattern reproducibility; TLC-Spectrophotodensitometry; cosine function